United Kingdom : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the United Kingdom. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2018)
This 2017 Article IV Consultation highlights that the economic growth in the United Kingdom has moderated since the beginning of 2017, reflecting weakening domestic demand. The sharp depreciation of sterling following the referendum has raised consumer price inflation, squeezing household real income and consumption. Business investment has been constrained. In the medium term, growth is projected to remain at about 1.5 percent under the baseline assumption of continued progress in Brexit negotiations that lead to an understanding on a broad free trade agreement and on the transition process. The baseline outlook is subject to a number of risks, including developments with Brexit negotiations; uncertainty about the recovery of productivity growth; and the current account deficit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet